Insect Pests of Medicinal and Aromatic Plants and their Management : an Overview - Sarma, Saurabh; Senthilkumar, N.; Das, Satyam K. R. (Indian Forester, 2008)
Medicinal and Aromatic Plants (MAPs) have great scope to achieve net higher returns and in international agribusiness which has an estimated growth rate of about 5-10 %. However, MAPs are facing danger of extinction due to the attack of some serious insect-pests, diseases, weeds, deforestation, extensive exploitation and harvesting from natural sources and lack of proper knowledge on those problems among majority of the people. Therefore there is an urgent need for through investigation on cultivation management of MAPs. Reports on insect pests of MAPs are meagre and scattered. There are about 40-45 major destructive insect-pest species found causing loss of about 50-60% damage to MAPs. Therefore, it is necessary to follow suitable management strategies involving IPM components of pest management. An overall literature review of insect pests of MAPs and their management is dealt herewith.